Attitudes towards open peer-review in the Croatian Medical Journal (PUBMET, 2025)
Background and aim: Traditional peer-review is anonymized and often criticized for being subjective, time consuming, not able to detect errors, and biased (Smith, 2006, Tennant, Ross-Hellauer, 2020). Coupled with the rise of open science, and the replication crisis, this has led to calls for more transparency and openness, including openness of peer-review and grant proposal evaluations. Open peer-review does not have a universal definition as there are myriad of practices represented under the term: open identities of the authors and reviewers, open review reports published alongside the article, open interaction and discussion between author(s) and reviewers, or open platforms where a review is facilitated by a different entity than the one where the paper is published (Ross- Hellauer, 2017, Bazdaric et al, 2021). Today, less than 2% of journals practice open peer-review (Responsible Journals, 2024), and the reasons for such a slow uptake are unclear, but attitudes of scientist likely play a role. Attitudes towards open peer-review were previously investigated with a validated questionnaire in a sample of Croatian scientists (n=541) that showed neutral and negative attitudes toward open peer-review and open peer-review in a small scientific community (Bazdaric et al, 2021). The goal of our study was to investigate attitudes of authors, reviewers and editors of the Croatian Medical Journal (CMJ), a diamond open access journal, regarding open peer review.Methods: Participants (n=4347) were invited to complete an anonymous online questionnaire through Google forms, where they also indicated their consent to participate in the study. The survey was open from March to May 2024, and we sent two reminders 14 days apart. We used the validated ATOPP questionnaire (Bazdaric et al, 2021) and added extra questions related to the Croatian Medical Journal, altogether 41 questions (21 attitudes on Likert scale 1-5; 9 open science practices, 11 demography and publishing). The open peer-review scale has two factors: open peer-review (6 questions) and open-peer review in a small scientific community (2 questions).Results: We received a total of 254 answers (response rate 6%), out of which 120 (47%) were authors, 25 (10%) reviewers, 57 (22%) authors and reviewers, and 26 (10%) in multiple editorial and author roles (editors, editorial board members and authors) and 19 (7%) did not want to declare their role. Of all participants, 128 (50%) were female, and the median age was 50 years (min 27-max 83) years. Participants came from 35 countries, however a little over half were from Croatia (54%). Participants’ attitudes towards open peer review were neutral (median score 3.2 (25 percentile 2.7-75th percentile 3.8), while their attitudes toward open peer review in a small scientific community were negative (median 2.3 (25 percentile 1.5-75th percentile 3.0). There were no gender differences in both constructs (P=0.259 and P=0.719, respectively). Over a third of participants (136, 53%) expressed they would like to see open peer-review in the journal, and 96 (38%) stated they would like to know the identity of their reviewers in the CMJ.Conclusion: Authors, reviewers, and editors in the CMJ are still very cautious towards open peer-review, especially in small scientific communities which is in line with previous results on a Croatian sample of scientists. It is important to raise awareness among journal editors and government agencies to increase peerreview transparency in journals and projects.
Keywords: attitudes; journals; open peer-review; open science; transparency